Near‐Field Energy Transfer into Silicon Inversely Proportional to Distance Using Quasi‐2D Colloidal Quantum Well Donors. Issue 41 (12th September 2021) - Humayun, Muhammad Hamza; Hernandez‐Martinez, Pedro Ludwig; Gheshlaghi, Negar; Erdem, Onur; Altintas, Yemliha; Shabani, Farzan; Demir, Hilmi Volkan
Abstract: Silicon is the most prevalent material system for light‐harvesting applications; however, its inherent indirect bandgap and consequent weak absorption limits its potential in optoelectronics. This paper proposes to address this limitation by combining the sensitization of silicon with extraordinarily large absorption cross sections of quasi‐2D colloidal quantum well nanoplatelets (NPLs) and to demonstrate excitation transfer from these NPLs to bulk silicon. Here, the distance dependency, d, of the resulting Förster resonant energy transfer from the NPL monolayer into a silicon substrate is systematically studied by tuning the thickness of a spacer layer (of Al2 O3 ) in between them (varied from 1 to 50 nm in thickness). A slowly varying distance dependence of d −1 with 25% efficiency at a donor–acceptor distance of 20 nm is observed. These results are corroborated with full electromagnetic solutions, which show that the inverse distance relationship emanates from the delocalized electric field intensity across both the NPL layer and the silicon because of the excitation of strong in‐plane dipoles in the NPL monolayer. These findings pave the way for using colloidal NPLs as strong light‐harvesting donors in combination with crystalline silicon as an acceptor medium for application in photovoltaic devices and other optoelectronic platforms. Abstract : The Förster resonant energy transfer (FRET) distance dependency of the decay kinetics of the donor nanoplatelets (NPLs) on silicon is studied. It is experimentally observed that the energy transfer efficiency scales with d −1 . The electromagnetic calculations explain that the observed FRET dependency emerges as a consequence of the electric field delocalization in the 2D layer of face‐down oriented NPLs.